2017
DOI: 10.12963/csd.17431
|View full text |Cite
|
Sign up to set email alerts
|

Disfluency, Speech Rate, and Communication Attitude Differences According to Gender and Age in Adults Who Do Not Stutter

Abstract: Objectives: Diverse speech samples should be analyzed due to variability in stuttering. However, there are limited Korean studies on the variability of disfluencies in adults who do not stutter for comparison with assessment data of adults who stutter. In addition, even though speech rate can be an indicator of treatment progress, differences in previous studies' methodologies make them difficult to employ in a clinic setting. The primary purpose of the current study is to determine whether there are differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…First, by identifying the most-searched terms, researchers can be led to the most contentious topics and themes in psycholinguistics research. In this study, they incorporated attention [ 108 ], child [ 109 ], physiology [ 110 ], young adult [ 111 ], and procedure [ 112 ]. They also included aphasia [ 113 ], deficit [ 114 ], prediction [ 115 ], constraint [ 116 ], and French [ 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, by identifying the most-searched terms, researchers can be led to the most contentious topics and themes in psycholinguistics research. In this study, they incorporated attention [ 108 ], child [ 109 ], physiology [ 110 ], young adult [ 111 ], and procedure [ 112 ]. They also included aphasia [ 113 ], deficit [ 114 ], prediction [ 115 ], constraint [ 116 ], and French [ 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acton (2011) showed that female's average um/uh (filled pauses) ratios were more than those of men in his two corpus-based examinations. Conversely, other researchers have suggested that gender does not affect disfluency in general (Andrade & Martins, 2011;Shin & Lee, 2017). Age as another factor that influences disfluency has been proven a controversial issue in the literature regarding speech disfluency (Leeper & Culatta, 1995;Menyhárt, 2003;Yairi & Clifton, 1972).…”
Section: Relationship Of Age and Gender On Disfluencymentioning
confidence: 98%
“…Other than these studies, some researchers have asserted female speakers speak more fl uently in certain conditions (when there is eye contact with the listener) than male speakers, and the gender of the listener does not infl uence speech disfl uency production (Branigan et al 1999). Andrade & Martins (2011) and Shin & Lee (2017) suggest that gender does not affect disfl uency production in general, and Laserna et al (2014) assert that gender does not affect mainly fi lled pause type of disfl uency production. Related to speech comprehension, Gósy (2001) has suggested that females show more sensitivity toward correct pause perception.…”
Section: Introductionmentioning
confidence: 99%